The aftermarket performance of initial public offerings - CHIRAPHOL, Chiyachantana N. (Institutional Knowledge at Singapore Management University, 2013)
This paper examines the aftermarket performance of initial public offerings (IPOs) and explores the underpricing of IPOs in an Asian emerging equity market using a comprehensive sample of IPOs. Our findings suggest that there exist a significant underpricing. Specifically, new issues have been offered at an average market-adjusted discount of about 20%. The magnitude of IPO underpricing is significantly larger for large firms, older firms and firms with small offering size.